An aluminum porphyrin complex with high activity and selectivity for cyclic carbonate synthesis1. Issue 5 (12th May 2015) - Qin, Yusheng; Guo, Hongchen; Sheng, Xingfeng; Wang, Xianhong; Wang, Fosong
<x xml:space="preserve">Abstract</x> A carefully designed aluminum porphyrin complex with a quaternary ammonium salt cocatalyst exhibits high activity and selectivity for cyclic carbonates synthesis.